Risiko Produksi Kentang dan Pengaruhnya Terhadap Pendapatan - Suminartika, Eti; Rasmikayati, Elly; Saefudin, Bobby Rachmat (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
West Java is one of the largest potato producers in Indonesia. Margamulya Village, Pengalengan District, Bandung Regency is the center for potato commodities in West Java Province. As a potato commodity center, of course the level of potato production in this area is very high, with this high production the resulting farming income should be able to improve the welfare of the farmers. However, the fact is that income from potato farming is still unstable. There are various factors that cause this phenomenon, one of which is the existence of risk factors in farming this commodity. Based on this background, this research aims to determine the effect of risks in potato production on farming income. This research uses quantitative methods with multiple linear regression analysis tools. Respondents in the research were 65 potato farmers in Margamulya Village, Pengalengan District, Bandung Regency. The results of this research reveal that the majority of potato farmers in Margamulya have a high level of risk in terms of seed costs, fertilizer costs (Cage, NPK, Urea and KCL), pesticide costs and labor costs, while Fungicide and Herbicide costs have a low level of risk. Based on the results of the regression analysis, 15 of the 17 production factors and production risks showed a significant influence on potato farming income. Then, of these 15 factors, all production risk factors have a significant effect on potato farming income, some have a positive effect and some have a negative effect.